PERSENAN sebagai instrumen dakwah di pasar tradisional (strategi loyalitas pelanggan oleh pedagang pasar) - Bambang Subandi subandi; Herma Musyanto (Sekolah Ilmu Dakwah dan Komunikasi Islam (STIDKI) Ar Rahmah, 2018)
Persenan is a parcel given by trader to customers toward at Great Day of Idul Fitri. The goal of persenan is to defense customers loyalty. This research aims to describe three ploblems about persenan and customers loyalty. First, how is persenan constructed by traders for customer loyalty in Pandan market of Mojokerto. Second, what type of persenan practiced by trader of Pandan market in Mojokerto to defense customer loyalty. Third, how can persenan defense customer loyalty. To overcome those problem, the research used qualitative approach. The technical of data discover used deep structure question, participant observation, and documenting. The data analyzed by reduct data, display data, and conclusion drawing. Informan of the research was trader that has more than 50 customers. The informan also gives persenan every toward Idul Fitri.The research results three points. First, trader constructed persenan as connection between himself dan his customer (externality). If the connection is like buyer dan seller, persenan constructed as gift (internality). If the connection is more chummy untill as close-friend, (objectivity), persenan constructed as friendship symbol (internality). If the connection is brotherhood (objectivity), persenan constructed as affection symbol (internality). The dominant factors in Pandan market are persenan constructed as gift and friendship symbol.(internality). Second, type of persenan given trader in Pandan market to his customer pressed customer satisfication. There are three factors of customer satisfication on persenan: given toward Great Day of Idul Fitri, based on amount of selling, and based on customer needs. Third, Persenan is not determinat factor of customer loyalty. There are other factors had influence on customer loyalty: easy price, take care of customer, and full stock. Therefor, level of customer loyalty in Pandan market untill latent loyalty, because customer divided selling to other trader. The research also recommended to Head of Pandan Market to keep of togetherness among traders. Other side, the research hope continuing study on persenan in other perspective.